2018
DOI: 10.1007/s12035-018-1289-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ethanol Exposure Promotes Autophagy-Lysosome Pathway-Dependent ASIC1a Protein Degradation and Protects Against Acidosis-Induced Neurotoxicity

Abstract: Tissue acidosis is a common feature of brain ischemia which causes neuronal injury. Activation of acid-sensing ion channel 1a (ASIC1a) plays an important role in acidosis-mediated neurotoxicity. Acute ethanol administration has been shown to provide neuroprotective effects during ischemic stroke, but the precise mechanisms have yet to be determined. In this study, we investigated the effect of ethanol on the activity/expression of ASIC1a channels and acidosis-induced neurotoxicity. We showed that acute treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Our recent study showed that the neuroprotective effect of ethanol might be related to the regulation of ASIC1a expression in neurons against acidosis-induced neurotoxicity (Zhou et al, 2019b). It has been indicated that acute treatment of neurons with ethanol decreased ASIC1a protein expression and acid-induced [Ca 2+ ] elevation (Zhou et al, 2019b). Further evidence suggests that the downregulation of ASIC1a protein was mediated by degradation of the protein via the autophagy-lysosome pathway (Zhou et al, 2019b).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent study showed that the neuroprotective effect of ethanol might be related to the regulation of ASIC1a expression in neurons against acidosis-induced neurotoxicity (Zhou et al, 2019b). It has been indicated that acute treatment of neurons with ethanol decreased ASIC1a protein expression and acid-induced [Ca 2+ ] elevation (Zhou et al, 2019b). Further evidence suggests that the downregulation of ASIC1a protein was mediated by degradation of the protein via the autophagy-lysosome pathway (Zhou et al, 2019b).…”
Section: Chemicalsmentioning
confidence: 99%
“…Tissue acidification and its associated activation of ASIC1a are common features of cerebral ischemia (Xiong et al, 2004). Our recent study showed that the neuroprotective effect of ethanol might be related to the regulation of ASIC1a expression in neurons against acidosis-induced neurotoxicity (Zhou et al, 2019b). It has been indicated that acute treatment of neurons with ethanol decreased ASIC1a protein expression and acid-induced [Ca 2+ ] elevation (Zhou et al, 2019b).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…CysC is a critical determinant accounting for endogenous neuroprotection and is a promising agent for the therapy of stroke, which is mediated by preserving lysosomal membrane integrity [84]. Acute ethanol exposure alleviates acidosis-induced neurotoxicity after cerebral ischemia, which is mediated by increased acid-sensing ion channel 1a (ASIC1a) protein degradation through the autophagy-lysosome pathway [85] (Table 4).…”
Section: The Adverse Role Of the Autophagy-lysosome Pathwaymentioning
confidence: 99%
“…K48-linked ubiquitin chains are predominantly introduced to be a signal for the ubiquitin-proteasome pathway, while K63-linked ubiquitin chains are known as a signal for autophagic degradation [102,103]. Despite their mode of [85] Abbreviations: TLR4: toll-like receptor 4; PF-11: pseudoginsenoside-F11; CAV1: caveolin1; NLRP3: NOD-like receptor family pyrin domain-containing 3; HHcy: hyperhomocysteinemia; CysC: cystatin C; ASIC1a: acid-sensing ion channel 1a. Oxidative Medicine and Cellular Longevity function and that their ubiquitin tags for substrate recognition are different, there is crosstalk between the ubiquitinproteasome pathway and the autophagy-lysosome pathway in the pathogenesis of cerebral ischemia.…”
Section: The Crosstalk Between the Ubiquitin-proteasome Pathway And Tmentioning
confidence: 99%